2014
DOI: 10.1111/mmi.12477
|View full text |Cite
|
Sign up to set email alerts
|

An actin‐like protein is involved in regulation of mitochondrial and flagellar functions as well as in intramacrophage survival of Leishmania donovani

Abstract: SummaryActin-related proteins are ubiquitous actin-like proteins that show high similarity with actin in terms of their amino acid sequence and three-dimensional structure. However, in lower eukaryotes, such as trypanosomatids, their functions have not yet been explored. Here, we show that a novel actin-related protein (ORF LmjF.13.0950) is localized mainly in the Leishmania mitochondrion. We further reveal that depletion of the intracellular levels of this protein leads to an appreciable decrease in the mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…Following the reverse genetic approach, depletion of the intracellular levels of LdALP3 resulted in decreased mitochondrial membrane potential and the ATP content together with shortening of the flagellum length ( Singh et al, 2014 ). Similar shortening of the flagellum has also been observed earlier in case of LdCof and LdMyo13 heterozygous mutants ( Tammana et al, 2008 ; Katta et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the reverse genetic approach, depletion of the intracellular levels of LdALP3 resulted in decreased mitochondrial membrane potential and the ATP content together with shortening of the flagellum length ( Singh et al, 2014 ). Similar shortening of the flagellum has also been observed earlier in case of LdCof and LdMyo13 heterozygous mutants ( Tammana et al, 2008 ; Katta et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although morphologies of the LdCof and LdMyo13 mutants closely resembled the nonmotile clones of LdALP3 mutants, there were two distinct features that made them different from each other – (1) the flexible and fast wriggling flagellum of the LdALP3 mutants, which in case of LdCof and LdMyo13 mutants was completely immotile ( Tammana et al, 2008 ; Katta et al, 2010 ), and (2) the assembly of PFR (though poor) in LdALP3 mutants, which was absent in the LdCof and LdMyo13 mutants. Based on these facts, it has been concluded that LdALP3 perhaps operates through a mechanism, that appears to be different from the mechanisms through which actin-based LdMyo13 motor functions in assembly of the Leishmania flagellum ( Singh et al, 2014 ). However, a cross-talk between the actin-based LdMyo13 motor and LdALP3 operated mechanisms cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Live Leishmania cells were visualized under bright field of Olympus IX 81 microscope with FV1000 confocal system on grooved slides which provides the freedom of movement to the parasites. Flagellar movements of both treated and control cells were analyzed (Singh et al, 2014). Numerous fields were used, and the distribution of counting areas was chosen in a nonbiased manner along the total surface area of the cover-slip for graphical representation of the motile parasites.…”
Section: Cell Motilitymentioning
confidence: 99%